The Impact of the Taliban's Return to Power on the Stability of Public Security in Afghanistan - Asdiarti, Riwana; Burhanuddin, Agussalim (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. The Taliban's return to power in Afghanistan in 2021 has sparked concern for the Afghan people and the international community. The Taliban's takeover of power not only impacts the country's security situation, but also affects the stability of public security in Afghanistan. Through this research, public security becomes an important aspect in knowing the impact of the new Taliban power. This research uses a qualitative method with a literature review and uses the concept of human security as an analytical framework. This research shows that some of the Taliban's policies since returning to power tend to be repressive and discriminatory, creating insecurity in the form of human rights violations, fear and individual freedom. The results of this research have shown that public security conditions in Afghanistan under the Taliban's second rule have not shown any improvement compared to their first period of power in 1996-2001. Although the Taliban managed to reduce the incidence of armed violence, public security stability still far from stable. This condition arises from the existence of rules and restrictions on access to education, employment, and health. The Taliban also resorted to violence, with persecution, arbitrary arrest and detention of people. The Taliban also face internal and external challenges in their efforts to maintain the stability of public security in Afghanistan. Keywords: Taliban, Afghanistan, Public Security. Abstrak. Kembalinya kekuasaan Taliban di Afghanistan pada tahun 2021 telah memicu kekhawatiran bagi masyarakat Afghanistan dan dunia internasional. Pengambilalihan kekuasaan oleh Taliban tidak hanya berdampak pada situasi keamanan negara, tetapi juga berpengaruh terhadap stabilitas keamanan masyarakat di Afghanistan. Melalui penelitian ini, keamanan masyarakat menjadi aspek penting dalam mengetahui dampak kekuasaan Taliban yang baru. Penelitian ini menggunakan metode kualitatif dengan studi kepustakaan, serta menggunakan konsep keamanan manusia (human security) sebagai kerangka analisis. Penelitian ini menunjukkan bahwa beberapa kebijakan Taliban sejak kembali berkuasa cenderung bersifat represif dan diskriminatif, sehingga menciptakan ketidakamanan dalam bentuk pelanggaran hak asasi manusia, ketakutan, dan kebebasan individu. Hasil penelitian ini telah menunjukkan kondisi keamanan masyarakat di Afghanistan di bawah pemerintahan kedua Taliban, belum menunjukkan perbaikan yang lebih baik daripada periode pertama kekuasaan mereka pada tahun 1996-2001. Meskipun Taliban berhasil mengurangi insiden kekerasan bersenjata, namun stabilitas keamanan masyarakat masih jauh dari kestabilan. Kondisi tersebut muncul dari adanya aturan dan pembatasan terhadap akses pendidikan, pekerjaan, dan kesehatan. Taliban juga bertindak menggunakan kekerasan, dengan melakukan penganiayaan, penangkapan dan penahanan orang secara sewenang-wenang. Taliban juga menghadapi tantangan-tantangan internal dan eksternal dalam upaya menjaga stabilitas keamanan masyarakat di Afghanistan. Kata Kunci: Taliban, Afghanistan, Keamanan Masyarakat.